Phenotypic evolution of UNC80 loss of function. Issue 12 (11th August 2016) - Valkanas, Elise; Schaffer, Katherine; Dunham, Christopher; Maduro, Valerie; du Souich, Christèle; Rupps, Rosemarie; Adams, David R.; Baradaran‐Heravi, Alireza; Flynn, Elise; Malicdan, May C.; Gahl, William A.; Toro, Camilo; et al.
Abstract : Failure to thrive arises as a complication of a heterogeneous group of disorders. We describe two female siblings with spastic paraplegia and global developmental delay but also, atypically for the HSPs, poor weight gain classified as failure to thrive. After extensive clinical and biochemical investigations failed to identify the etiology, we used exome sequencing to identify biallelic UNC80 mutations (NM_032504.1:c.[3983‐3_3994delinsA];[2431C>T]. The paternally inherited NM_032504.1:c.3983‐3_3994delinsA is predicted to encode p.Ser1328Argfs*19 and the maternally inherited NM_032504.1:c.2431C>T is predicted to encode p.Arg811*. No UNC80 mRNA was detectable in patient cultured skin fibroblasts, suggesting UNC80 loss of function by nonsense mediated mRNA decay. Further supporting the UNC80 mutations as causative of these siblings' disorder, biallelic mutations in UNC80 have recently been described among individuals with an overlapping phenotype. This report expands the disease spectrum associated with UNC80 mutations. © 2016 Wiley Periodicals, Inc.